EGALITE Newsletter : equality for gays and lesbians in the European institutions (Brussels: EGALITE)
"Fonds Suzan Daniel (FSD)Periodiciteit : tweemaandelijks ; vanaf (1997) 21 : driemaandelijksRedactie : Wetstraat 200, 1049 Brussel"